Kelayakan Buku Pengayaan Berbasis Penelitian: Pengaruh Dosis Kalium (K) terhadap Performansi Genotipe Kedelai Tahan Cowpea Mild Mottle Virus (CpMMV) - Tyas, Intan Lestari Mulyaning; Siti Zubaidah; Heru Kuswantoro (Journal of Practice Learning and Educational Development, 2024)
This research was conducted to facilitate the availability of additional information for students at Agriculture vocational schools of valid enrichment books, which can support the implementation of enrichment programs so information more relevant, contextual and focused on learning objectives. The enrichment book was developed based on the use of varying doses of Potassium (K) in CpMMV-resistant soybean plants. The development model used is ADDIE, and this enrichment book has been tested for the feasibility of its material aspects, presentation, language and graphics by validators. The overall average score of the validation results was 88.45 with the meaning of very good, with details: material aspect 91.7 (very good), presentation 88.7 (very good), language 84.7 (good), graphics 88.7 (Very good). The enrichment book that has been developed is declared feasible and ready to be used in learning activities, especially enrichment programs in at Agriculture vocational schools.